2017
DOI: 10.3390/catal7120382
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preparation Method on the Structure and Catalytic Activity of Ag–Fe2O3 Catalysts Derived from MOFs

Abstract: Abstract:In this work, Ag-Fe 2 O 3 catalysts were successfully prepared using several different methods. Our main intention was to investigate the effect of the preparation methods on the catalysts' structure and their catalytic performance for CO oxidation. The catalysts were characterized by X-ray diffraction (XRD), N 2 adsorption-desorption, transmission electron microscopy (TEM), X-ray photoelectron spectroscopy (XPS), H 2 -temperature program reduction (H 2 -TPR) and inductively coupled plasma optical emi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 59 publications
(88 reference statements)
0
11
0
Order By: Relevance
“…This peak can be related to the degree of dispersion of metal. The stronger intensity absorption band of Fe2O3 was detected, suggesting that iron was in highly dispersive state, no large iron oxide particles aggregated in the sample [43,44]. It was noted that the Fe/W-CeO2-P catalyst showed the weakest intensity peak of Fe2O3, suggesting the highest dispersion of iron in Fe/W-CeO2-P catalyst.…”
Section: Xpsmentioning
confidence: 94%
“…This peak can be related to the degree of dispersion of metal. The stronger intensity absorption band of Fe2O3 was detected, suggesting that iron was in highly dispersive state, no large iron oxide particles aggregated in the sample [43,44]. It was noted that the Fe/W-CeO2-P catalyst showed the weakest intensity peak of Fe2O3, suggesting the highest dispersion of iron in Fe/W-CeO2-P catalyst.…”
Section: Xpsmentioning
confidence: 94%
“…nitro-compounds hydrogenations,244,263,276,280,281,285,[304][305][306][307] alcohols oxidations,247,293,297 CO oxidation250,259,[264][265][266][267][268][277][278][279]289,[294][295][296]301,246,254,285,[290][291][292]309,310 Ox, achieved by the direct calcination of a bimetallic Ce(Cu)-MOF at 600 °C for 3 h. The catalytic activity was tested using a continuous flow fixed-bed micro-reactor at atmospheric pressure with a CO/O2/N2 mixture in a volume ratio of 1:10:89. The authors found the CeO2-CuO exhibited a high catalytic activity in comparison to that of Ce-Cu-Ox; an almost 80% CO conversion for CeO2-CuO at 250 °C and only 22% for Ce-Cu-Ox derived from the Ce(Cu)-MOF.…”
mentioning
confidence: 99%
“…The binding energy peaks of Fe 2p 3/2 and Fe 2p 1/2 were found around 711.10 to 710.69 eV and 724.91 to 723.87 eV, respectively, as shown in Figure A, and the carrier was thus composed of Fe 2+ and Fe 3+. As analyzed by fitting the curves obtained from the XPS spectra, the integral area ratios of Fe 2+ and Fe 3+ around the Fe 2p 3/2 peak were close to 1:1 for Pt/FeHAP‐CB3, Pt/FeHAP‐CB2 and Pt/FeHAP‐CB1.…”
Section: Resultsmentioning
confidence: 98%